(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The analysis clearly revealsthe limited success of India in ensuring the minimum levels of education forits population. Despite considerable progress, sharp disparities continue toexist between male and female literacy levels. There is an urgent need thatgovernment has to address various aspects for improving literacy and elementaryeducation. Like firstly, more resources have to be allocated to educationparticularly primary education with the international norm of 6% of GDP.Secondly, the quality of education in terms of curriculum, betterinfrastructure and teaching has to be improved. Thirdly, social mobilisation ofthe community against child labour. Fourthly, emphasis on generation ofproductive employment and minimum wages would reduce the households’ dependenceon children. Fifthly, Mid-Day Meal Scheme can help increase attendance, improvenutrition reduce dropout rates. Others like, Pre-school education in IntegratedChild Development Services, involvement of Panchyats and NGOs, high returns toeducational investment, removing institutional constraints, reduction in schoolfees of private institutions, reduction in distance to school, conditional cashtransfers etc. promote primary education. Instead of piece-meal ad-hocapproaches, government should adopt comprehensive policy which will help inachieving the goal of “Education for all” in given short period.